2017
DOI: 10.1016/j.ijsolstr.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Full-range FRP failure behaviour in RC beams shear-strengthened with FRP wraps

Abstract: , Full-range FRP failure behaviour in RC beams shear-strengthened with FRP wraps, International Journal of Solids and Structures (2017), doi: 10.1016/j.ijsolstr.2017 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 39 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Because of the high tensile strength, light weight, and convenient construction, BF/EP composite material can be used as a new type of reinforcement material and applied to repair and strengthening of concrete structure and steel structure in civil engineering [7]. For example, the reinforcement material is glued to the tensile area of concrete component (walls, beams, slabs, and columns), which can effectively improve its carrying capacity, avoid excessive deformation of the cross section, and prevent the crack expansion [8][9][10]. And in the shear area of the concrete beam, reinforced material can effectively improve its shearing capacity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the high tensile strength, light weight, and convenient construction, BF/EP composite material can be used as a new type of reinforcement material and applied to repair and strengthening of concrete structure and steel structure in civil engineering [7]. For example, the reinforcement material is glued to the tensile area of concrete component (walls, beams, slabs, and columns), which can effectively improve its carrying capacity, avoid excessive deformation of the cross section, and prevent the crack expansion [8][9][10]. And in the shear area of the concrete beam, reinforced material can effectively improve its shearing capacity [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mostafa et al predicted the debonding load for FRP strengthened reinforced concrete members and proposed a nonlinear analytical model to determine the interfacial shear and normal stresses at the FRP–concrete interface for reinforced concrete beams externally strengthened with CFRP sheets [32,33]. Chen et al [34] presented an analytical study on the progressive failure of FRP wraps in strengthened beams. In their research study, the debonding and the subsequent rupture processes were derived, and the FRP contribution to the shear capacity of the beam was quantified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The increase in the shear strength of RC beams was in the range of 10-70% compared to the control beams. Chen et al [35], studied the failure of FRP wrapping types (full wrapping, side, and Ustrips) in an FRP strengthened RC beams and how it affects the shear behavior of the beam was examined by considering the shear crack opening and tried to be determined by the analytical study. They found that in the shear strengthening of FRP, the first crack load occurs at a higher shear load than the control beams In this study, an experimental program was planned and executed to investigate the effect of strengthening self-compacting concrete beams using carbon fiber-reinforced polymer (CFRP) fabrics with different U-wrapping CFRP with different widths and densities in shear.…”
Section: Introductionmentioning
confidence: 99%